2020
DOI: 10.3906/tar-1902-22
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of metamitron efficiency for postbloom thinning of young ‘Gala’ and ‘Golden Delicious’ apple trees

Abstract: Introduction Establishing new apple orchards using well-feathered apple trees has recently become common practice. In favourable growing conditions, these trees can produce high yield in the second leaf, achieving full productivity in the fourth leaf (Radivojevic et al., 2014). High-quality trees of the cultivars 'Gala' and 'Golden Delicious' during the establishing period frequently produce an excessive number of fruitlets but this can be insufficient to guarantee fruit of good marketable size at harvest (Bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
1
5
0
1
Order By: Relevance
“…The largest apple producers in Europe are Poland (25.00%), Italy (19.20%), and France 15.50% [1]. Consequently, apples remain one of the most widely grown and consumed fruits in the world, and their processed products are widely used in the production of food supplements, food industry products, and beverages [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…The largest apple producers in Europe are Poland (25.00%), Italy (19.20%), and France 15.50% [1]. Consequently, apples remain one of the most widely grown and consumed fruits in the world, and their processed products are widely used in the production of food supplements, food industry products, and beverages [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…In this experiment, combined application of the preparations MaxCel/Brevis produced the best thinning effects through a distinct decrease of yield and improvement of most of the analysed quality parameters of apples, relative to the control. Also Radivojevic et al (2019) demonstrated that the use of a mixture of BA and metamitron can alleviate the unfavourable effect of low temperatures (below 10°C by night and below 20°C in daytime). The application of that mixture caused a significant increase in fruit dimensions and an improvement of yield structure.…”
Section: Resultsmentioning
confidence: 98%
“…Other authors have reported that the minimum temperature affects metamitron efficacy. Radivojevic et al [46] showed the positive thinning efficacy of a single application at 6-15 mm of metamitron, with minimum temperatures above of 10 • C. Gonzalez et al [2] concluded that, when the average night temperature was higher than 14 • C for 4 days after a single application between 7.5 and 13.5 mm, the efficacy of metamitron was high. Clever [38] estimated that thinning efficacy was higher when the night-time temperature was above 10 • C. However, their results were collected over a different period of days to that of this study (1 day before the spray and 1 or 2 days after the spray).…”
Section: Discussionmentioning
confidence: 99%